The use of CIPP model for evaluation of computational algorithm learning program - Hartati, S J; Sayidah, N; Muhajir (Journal of physics. Conference series, 2018)
The objective of this research was to evaluate the learning program of computational algorithm subject in two private universities in Surabaya. The evaluation was performed by using the theoretical framework of CIPP model. There were two research questions presented in this study: what is the research design to evaluate the learning program and what is the profile of the learning style-based computational algorithm learning program according to CIPP model. The results showed that the research design consists of 5 steps, which are: to determine the focus of the research, to collect the data, to test the instruments' validity and reliability, to analyse the data, and to draw a conclusion. Every research step is formulated based on 4 components, which are: context, input, process, and product. The learning program has several profiles. Firstly, the pre-required environment does not correspond with the characteristics of the population. Secondly, students' mathematical ability does not meet the qualification set in the lesson plan. Thirdly, the supporting learning facility and instruments are not sufficient. Next, the implementation of the lesson plan is adjusted according to students' condition. Lastly, the average of students' computational algorithm scores is 49. It is recommended to conduct matriculation program before the actual learning program for students that do not meet the pre-requirements stated in the lesson plan. The matriculation module consists of the basics of mathematical reasoning, which includes: arithmetic logics, algebraic logics, and mathematical logics.